Boosting Activity and Selectivity of CO2 Electroreduction by Pre‐Hydridizing Pd Nanocubes. Issue 49 (17th November 2020) - Chang, Qiaowan; Kim, Jeonghyeon; Lee, Ji Hoon; Kattel, Shyam; Chen, Jingguang G.; Choi, Sang‐Il; Chen, Zheng
Abstract: The electrochemical CO2 reduction reaction (CO2 RR) to syngas represents a promising solution to mitigate CO2 emissions and manufacture value‐added chemicals. Palladium (Pd) has been identified as a potential candidate for syngas production via CO2 RR due to its transformation to Pd hydride under CO2 RR conditions, however, the pre‐hydridized effect on the catalytic properties of Pd‐based electrocatalysts has not been investigated. Herein, pre‐hydridized Pd nanocubes (PdH0.40 ) supported on carbon black (PdH0.40 NCs/C) are directly prepared from a chemical reduction method. Compared with Pd nanocubes (Pd NCs/C), PdH0.40 NCs/C presented an enhanced CO2 RR performance due to its less cathodic phase transformation revealed by the in situ X‐ray absorption spectroscopy. Density functional theory calculations revealed different binding energies of key reaction intermediates on PdH0.40 NCs/C and Pd NCs/C. Study of the size effect further suggests that NCs of smaller sizes show higher activity due to their more abundant active sites (edge and corner sites) for CO2 RR. The pre‐hydridization and reduced NC size together lead to significantly improved activity and selectivity of CO2 RR. Abstract : The structure–property–activity relationship of PdH x during the CO2 reduction reaction (CO2 RR) is in situ elucidated. Under the CO2 RR conditions, both of the PdH0.40 and Pd nanocubes (NCs) are transformed into the stoichiometric PdH1 . However, compared with Pd NCs/C, PdH0.40 NCs/C presents less cathodic phase transformation (to PdH1 ), leading to the enhanced CO2 RR performance.